Etniczno-kulturowe styczności polskich i litewskich zwyczajów obrzędowych w pobożności do św. Kazimierza - Vaičiūnas, Vytautas Steponas; Motuzas, Alfonsas (Śląskie Studia Historyczno-Teologiczne, 2006)
Traditional folk devotional practices in nowadays Lithuania are found in the Church calendar, among the prayers, hymns and songs of national feasts, memorable days or additional devotions (Hours of Our Lady, the Rosary of Our Lady and of Jesus‘ Name, performed orally or by singing, Samogitian Calvaries, Stations of the Cross, Lamentations on the Passions of Christ and Mourning Psalms in commemoration of the dead. Among them, there are special feasts of different Lithuanian saints and the blessed. In the course of centuries, Lithuania had a lot of prominent people, wise rulers, brave men or sages. Among them there are blessed archbishop George Matulaitis and Michael Giedraitis who are on the way to beatification, but so far not proclaimed as saints. The only Lithuanian saint is St. Casimir. There are quite a lot scientific theological, historical, art research (iconographic) materials about the cult of St. Casimir either in Lithuania, or all over the world, but practically there no materials about the folk devotions and rituals, concerning St. Casimir. Historical sources claim the cult of St.Casimir to be of local origin, i.e., worshiped only in separate regions, having either historical or neighbouring contacts with Poland. Historical facts confirm that: Pope Clement VIII by his breve (1602 XI 07) raised the feast of St. Casimir in Lithuania and Poland to a higher liturgical degree (sub ritu dublici), in other words, proclaimed his cult as local, i.e., for Lithuania and Poland. His successor, Pope Paul V, made it universal and included St. Casimir’s prayers into the Missal and breviary. In 1636 Pope Urban VIII proclaimed St. Casimir the patron of Lithuania, and allowed his feast to be celebrated with solemn liturgy. That is why he bears the name Magnus Ducatus Lituanus. As there are close Catholic contacts between Poland and Lithuania, the aim of the research is to reveal ethno-cultural contacts of St. Casimir’s devotional practices in Poland and Lithuania. In order to reach the purpose, such tasks were raised: firstly, to reveal St. Casimir’s devotional practices in Lithuania; then, to set the origin of these practices and their intercultural ethnic ties. The research done allows to make such conclusions: firstly, the cult of St. Casimir in Lithuania is of local origin, i.e., he is worshiped in separate Lithuanian regions, having either historical, or neighbouring contacts with Poland (Highlands and Suvalkija); secondly, St. Casimir’s devotions consist of 10 customs. They are: 12 stations of St. Casimir’s pious life, processions with palms; women, hiding their hair and faces under a kerchief and walking afoot as a symbol of chastity; a cloth, that vestured St. Casimir’s relics, put into pieces and venerated; fasting; giving alms to the beggars; lying cruciform on the ground, playing with signal musical instruments and singing of hymns; thirdly, from 10 ritual customs, 6 are of Polish origin, 4 – of local origin, 3 – from the teachings of the Church or the personal life of St. Casimir; fourthly, the most ethnographically rich region is eastern and south-eastern Lithuania (Highlands and Dzūkija): 4 are in Vilnius diocese, 2 – in Panevėžys diocese and 1 – in Kaunas archdiocese. Suvalkija (Vilkaviškis diocese) has got 2 ritual customs. All the ethnographic regions have a common ritual custom – singing of hymns. The fifth thing is ritual customs of local origin: women, hiding their hair and faces under a kerchief and walking afoot as a symbol of chastity, a cloth, that vestured St. Casimir’s relics, put into pieces and venerated. Using of these customs witness the respect and love of Lithuanian Catholics to St. Casimir. The sixth thing is that, during the missions of Jesuit sodality, came solemn processions with the palms in honour of St. Casimir. And the last conclusion is that Polish religious culture influenced Lithuanian folk devotions in forming such ritual customs as: walking of twelve stations, devoted to St. Casimir’s pious life, special prayers, said to his honour, singing of special hymns or other sonic expressions, like playing the signal instruments. The results of the research prove the thesis, that devotions to St. Casimir are the obelisk of Polish and Lithuanian spirituality, a symbol of fights for religious freedom, against paganism, Protestantism, Islam and Orthodoxy. They were influenced by the historical – geopolitical situation, by the Jesuit order in Lithuania with their sodalities, colleges and wide area of their missions.